EFEKTIVITAS PEMBERDAYAAN ANAK-ANAK KORBAN BENCANA GEMPA DAN TSUNAMI ACEH DAN SUMATERA UTARA OLEH YAYASAN RUMAH ANAK MADANI DI DESA MANUNGGAL KECAMATAN LABUHAN DELI KABUPATEN DELI SERDANG - ARI KURNIAWAN (Welfare StatE, 2013)
This research entitled "Effectiveness of Empowering Children Victims of Earthquake and Tsunami in Aceh and North Sumatra by the Yayasan Rumah Anak Madani in the village Manunggal Civil District Labuhan Deli Serdang regency". This study aimed to determine the effectiveness of empowerment of children affected by the earthquake and tsunami in Aceh and North Sumatra by the Yayasan Rumah Anak Madani through four program areas: education, skills training, parenting, and health. Results of this study are expected to be a reference source for the author's own theory, readers, and especially for the foundation as a reference for policy development and the implementation model of empowerment in the Yayasan Rumah Anak Madani. The study was conducted at the Yayasan Rumah Anak Madani. This research is descriptive, where the population in this study were all foster children of Yayasan Rumah Anak Madani who have been victims of the earthquake and tsunami in Aceh and North Sumatra in 2004 and as many as 29 people, so all the population data was taken. Data collection techniques to the study of literature and field studies. Empowerment in terms of education, skills training and talent, care services, and health services. The data obtained in the field and then analyzed and compiled in a single table after it is explained qualitatively. The results show conclusively that the ministry of education, training, skills and talents, and effective health care, while less effective caregiving services. The foundation should pay more attention to shortcomings in the care services provided to foster children and the development of better services to other areas in order to achieve the purpose of the foundation up. Keywords: Effectiveness, Empowerment, Child